2022
DOI: 10.1155/2022/9439957
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior and Impact of Heterogeneous Investors in China’s Stock Index Futures Market: An Agent‐Based Model on Cross‐Market Trades

Abstract: Since the period of unusual volatility in China’s A-share market in 2015, there has been an ongoing discussion about the role of stock index futures in the A-share market. There is no unified consensus among academics and industry insiders on whether stock index futures affect spot market volatility. Using agent-based modeling, we construct a theoretical model of the order book of the stock index futures market to assess the microbehavior of speculators, arbitrageurs, and hedgers in this market. We then calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The agent-based modeling method has been widely used to evaluate the effectiveness of investment portfolios, predict market volatility, and other aspects. Yang et al (2022) [17] discussed the use of the method in studying market microstructure, financial crises, and market regulation. Dehkordi et al (2023) [18] provided a comprehensive overview of the use of agent-based modeling in finance, including its strengths and weaknesses.…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…The agent-based modeling method has been widely used to evaluate the effectiveness of investment portfolios, predict market volatility, and other aspects. Yang et al (2022) [17] discussed the use of the method in studying market microstructure, financial crises, and market regulation. Dehkordi et al (2023) [18] provided a comprehensive overview of the use of agent-based modeling in finance, including its strengths and weaknesses.…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…For instance, Xiao and Wu [ 22 ] found that informed traders tend to trade in the stock market when the information reflects the operating conditions of a limited number of companies and in the futures market when the information reflects the overall market position. Similarly, Yang et al [ 23 ] used agent-based modeling to build a theoretical model of the order book and discovered that speculators, arbitrageurs, and hedgers play distinct roles in Chinese markets. Furthermore, Zhou & Li [ 24 ] constructed a multiagent spot-futures market model to examine the micromechanics of shock transfer and observed that arbitrageurs play a substantial role in spot-futures market contact and that appropriate arbitrage trading during crises can aid in reducing the positive basis and preventing the further spread of crises.…”
Section: Introductionmentioning
confidence: 99%